Laboratory medicine: from student days to clinical practice - N. V. Ryazantseva; I. V. Kulagina; T. T. Radzivil; N. P. Kovalyova (Бюллетень сибирской медицины)
A problem of interaction of laboratory diagnostics specialists and clinicians in diagnostic and treatment processes has been raised. The viewpoint of authors on the expediency of laboratory medicine fundamentals teaching in doctors’ faculties of medical colleges has been presented.